Carbon stock dynamics in Sheka forest biosphere reserve, Ethiopia: A 60-year trajectory (1990–2050) and its implications for ecosystem services and conservation - Bernhau, Yericho; Dalle, Gemedo; Workeneh, Dejene Sintayehu; Kelboro, Girma; Nigussie, Abebe; Gitma, Ginjo (Elsevier BV, 2025)
Biosphere reserves are intended to conserve ecosystems and enhance carbon sequestration, yet their long-term effectiveness remains understudied. This study aimed to evaluate carbon stock changes in Ethiopia’s Sheka Forest Biosphere Reserve from 1990 to 2050, along with their implications for ecosystem services and conservation. Forty-nine plots were established along three transects to evaluate vegetation structure and soil characteristics. Woody species diversity was measured using the Shannon–Wiener diversity index, and carbon stocks were estimated via allometric equations and the Walkley-Black method. Future land use and carbon stock changes were projected using the CA-Markov and InVEST model, respectively. Results show that live trees held the highest carbon stock (295.48±43.24 tons C ha⁻¹), followed by soil organic carbon (279.48±8.73 tons C ha⁻¹), with lesser contributions from litter, stumps, and deadwood. Carbon stock was positively correlated with woody species diversity and varied significantly by topography and land use type. From 1999 to 2020, total carbon stock declined by 2.5 tons C ha⁻¹ per year, with projections suggesting an increased annual loss of 3.1 tons C ha⁻¹ through 2050. Carbon stock continues to decline despite the designation of biosphere reserves, even though forests are essential for carbon storage, biodiversity, and ecosystem functions. Enhanced conservation measures such as halting deforestation, promoting community-based forest management, and encouraging sustainable resource use are critical to reversing this trend and sustaining ecosystem services.